2020
DOI: 10.33448/rsd-v9i12.11056
|View full text |Cite
|
Sign up to set email alerts
|

Predição do comportamento farmacocinético, toxicidade e de atividades biológicas de alcaloides isolados de Geissospermum laeve (Vell.) Miers

Abstract: O presente trabalho realizou estudos in silico com o objetivo de predizer as atividades farmacocinéticas, toxicológicas e biológicas de alcaloides isolados de Geissospermum laeve. Os desenhos das moléculas e análises físico-químicas foram feitas no ChemSketch e Chemicalize.org, o comportamento farmacocinético e toxicidade foram realizadas  por comparação nos programas PreADMET  e  PASS  online. Os resultados descrevem que as moléculas demonstram bom comportamento farmacocinético e biodisponibilidade, com desta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The predicted ADMET properties of anonaine with different parameters analyzed by the PreADMET tool shown in Supplementary Table 2, suggest that anonaine has moderate toxicity and no carcinogenic potential. All values obtained in the results with anonaine were compared to standard values reported in the literature (Ames et al, 1972;Yee, 1997;Van De Waterbeemd and Gifford, 2003;Alliance, 2016;Wadapurkar et al, 2018;Ferreira et al, 2020;Pereira, 2021;Tong et al, 2021). Also, it is suggested that natural alkaloid anonaine is less toxic to mammals than cypermethrin.…”
Section: Discussionmentioning
confidence: 84%
“…The predicted ADMET properties of anonaine with different parameters analyzed by the PreADMET tool shown in Supplementary Table 2, suggest that anonaine has moderate toxicity and no carcinogenic potential. All values obtained in the results with anonaine were compared to standard values reported in the literature (Ames et al, 1972;Yee, 1997;Van De Waterbeemd and Gifford, 2003;Alliance, 2016;Wadapurkar et al, 2018;Ferreira et al, 2020;Pereira, 2021;Tong et al, 2021). Also, it is suggested that natural alkaloid anonaine is less toxic to mammals than cypermethrin.…”
Section: Discussionmentioning
confidence: 84%
“…For the oral toxicity study, the ProTox-II online server [ 52 ] was used, based on the 50% lethal dose (LD 50 ), following the classification of this potential into the following classes: fatal if ingested—class I (LD 50 ≤ 5mg/kg) and class II (LD 50 between 5 and 50 mg/kg); toxic if ingested—class III (LD 50 between 50 and 300 mg/kg); harmful if ingested—class IV (LD 50 between 300 and 2000 mg/kg); may be harmful if ingested—class V (LD 50 between 2000 and 5000 mg/kg); non-toxic—class VI (LD 50 ≥ 5000 mg/kg) [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…All structures showed low permeability in MDCK cells, with the following results: isoscutelarein A: 0.99703, theograndin I: 0.0448005, Theograndin II: 0.045115, hypolaetin A: 0.542677 and hypolaetin B: 0.0446855 (Table 2). MDCK (Madin-Darby canine kidney) cells come from the kidneys of Madin-Darby dogs which, when grown in the laboratory, form structures like ducts, differentiating into columnar epithelial cells with semipermeable membranes with junctions similar to Caco-2 cells, exhibiting features that resemble the epithelial cells found in kidney tubules (Ferreira, Brandão & Dolabela, 2020). MDCK cells are widely used to study renal distal tubular physiology through the transport of substances and ions (Sousa, Freitas & Storpirtis, 2007).…”
Section: Permeability In Mdck Cellsmentioning
confidence: 99%
“…They are frequently used in substance toxicity studies, as they play a fundamental role in evaluating the harmful effects of different substances in the aquatic environment, being very sensitive to toxic agents. Furthermore, they are important in many food chains, being a significant source of food for fish, in addition to having a relatively short life cycle, a significant parameter for evaluating acute and subchronic toxicity (Ferreira et al, 2020).…”
Section: Daphnia Spmentioning
confidence: 99%